Formation and development of Russian university technical education - I. . Fedorov; V. . Baltyan (Высшее образование в России)
The article sums up the results of development of Russian university technical education system for the last 20 years. The authors mark out its specific features, and give a detailedanalysis of the main principles of organization of learning and research process at technical university, such as humanitarization, fundamentalization and professionalization. The complex program for the development of university technical education in Russia on the contemporary stage is presented.